The effect of foreign institutional ownership on corporate tax avoidance: international evidence - Iftekhar Hasan; Incheol Kim; Haimeng Teng; Qiang Wu (Bank of Finland, 2016)
This study examines whether foreign institutional investors (FIIs) help explain variation in corporate tax avoidance and whether mechanisms such as tax morality, investment horizon, and corporate governance underlie the relation between FIIs and tax avoidance. We find robust evidence that FIIs are negatively associated with corporate tax avoidance. Moreover, this negative association is dominated by FIIs from countries with high tax morality, FIIs with long-term investment horizons, and FIIs from countries with high corporate governance quality. We conclude that FIIs play an active role in shaping corporate tax avoidance policy.
URN:NBN:fi:bof-201608241387
Keywords: G23; G32; H26; M41; 330